2018
DOI: 10.1111/1541-4337.12355
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for the Prevention and Management of Helicobacter pylori Infection

Abstract: Helicobacter pylori is the main pathogen that induces chronic gastritis, peptic ulcers, atrophic gastritis, and other gastric disorders, and it is classified as a group I carcinogen. To eradicate H. pylori infection, triple therapy consisting of two antibiotics and a proton pump inhibitor is the most widely recommended first-line therapeutic strategy. Antimicrobial resistance to antibiotics contained in triple therapy could lead to therapeutic regimen failures. Recent studies showed that many natural products,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 141 publications
(119 reference statements)
3
39
0
Order By: Relevance
“…pylori can cause diseases only if successfully colonized. The optimal growth pH for H. pylori is 8.5, whereas the bacteria can survive for only approximately 30 min under extremely acidic environments, such as gastric cavity [18,19]. The ability of H. pylori to transiently resist gastric acid and pass through the gastric mucous layer, quickly reaching the pH-neutral environment, mainly depends on its urease, chemotaxis system, flagella, and spiral morphology ( Figure 1) [20].…”
Section: Colonization Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…pylori can cause diseases only if successfully colonized. The optimal growth pH for H. pylori is 8.5, whereas the bacteria can survive for only approximately 30 min under extremely acidic environments, such as gastric cavity [18,19]. The ability of H. pylori to transiently resist gastric acid and pass through the gastric mucous layer, quickly reaching the pH-neutral environment, mainly depends on its urease, chemotaxis system, flagella, and spiral morphology ( Figure 1) [20].…”
Section: Colonization Mechanismsmentioning
confidence: 99%
“…Recent studies have shown that the eradication of H. pylori in infected asymptomatic individuals at all ages can reduce the occurrence of gastric cancers [6]. Various virulence factors and virulence genes of H. pylori, such as cytotoxin-associated gene A protein (CagA), vacuolating cytotoxin protein (VacA), duodenal ulcer promoting gene (DupA), and urease play the key role in injuring host tissues and inducing gastrointestinal diseases [19].…”
Section: H Pylori Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating studies have suggested that Helicobacter pylori infection can cause various gastric diseases, such as chronic gastritis, peptic ulcers, and atrophic gastritis. The Helicobacter pylori infection is highly related to the pathogenesis of gastric cancer, particularly the intestinal type [95][96][97]. It was reported that infection with cytotoxin-associated gene antigen cagA + strains of Helicobacter pylori might lead to severe gastric inflammation and gastric cancer [98,99].…”
Section: Inhibition Of Helicobacter Pylorimentioning
confidence: 99%
“…This might lead to the suggestion that BabA and other binding proteins such as SabA are involved in carcinogenesis 24 . This protein was reported to be necessary for H. pylori replication and nutrient acquisition 25,26 , it has been estimated in population with the highest incidence of gastric cancer worldwide as in East Asia 22 27,28 . To explore that computational aid drug design (CADD) can play an important in drug design and discovery using different approaches, among these Structure-Based Drug Design (SBDD), since a lot of 3D structures are now available.…”
Section: Introductionmentioning
confidence: 99%